PEASANT ECONOMY IN MALAYSIA: THE ADVENT OF CAPITALISM AND THE EXPANSION OF MONEY ECONOMY INTO AGRICULTURE IN COLONIAL MALAYA (History Department, Semarang State University and Historian Society of Indonesia, 2018)
This paper examines the advent of capitalism in rural economy by using the commercialization of the peasant economy in colonial Malaya period. It reflects the historical development with reference to the increase of money economy within the society who was mostly the peasants. It means that mostly all means of transaction exchanges were increasingly conducted in monetary form. Following this pattern, this phenomenon is applied to the years between 1850 and 1941 in Malaya as it was signified by the transition from traditional to modern orientation in the economic aspects of the Malay society with special attention to peasant community. Such economic changes that were manifested by the increase of money economy can be seen in a labour utilization and the change in land ownership, the commercial orientation in paddy cultivation, agricultural credit facilities and the penetration of commercialism in the Malay society as a whole.Â Â Makalah ini meneliti kemunculan kapitalisme dalam ekonomi pedesaan dengan menggunakan komersialisasi ekonomi petani pada masa kolonial Malaya. Ini men-cerminkan perkembangan historis dengan mengacu pada peningkatan ekonomi uang di masyarakat yang kebanyakan adalah petani. Artinya, kebanyakan sarana pertukaran transaksi semakin banyak dilakukan dalam bentuk moneter. Mengikuti pola ini, fenomena ini diterapkan pada tahun-tahun antara tahun 1850 dan 1941 di Malaya karena ditandai dengan transisi dari orientasi tradisional ke modern dalam aspek ekonomi masyarakat Melayu dengan perhatian khusus pada masyarakat petani. Perubahan ekonomi seperti itu yang dimanifestasikan oleh peningkatan ekonomi uang dapat dilihat pada pemanfaatan tenaga kerja dan perubahan kepemilikan tanah, orientasi komersial dalam penanaman padi, fasilitas kredit pertanian dan penetrasi komersialisme dalam masyarakat Melayu secara keseluruhan.Â